ANALISIS KELAYAKAN PENERBITAN OBLIGASI DAERAH SEBAGAI ALTERNATIF PEMBIAYAAN DAERAH UNTUK PEMBANGUNAN DAERAH PADA PEMERINTAH PROVINSI SUMATERA BARAT - Afridian Wirahadi Ahmad; Dea Rezky Amalia, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2021)
This study aims to analyse the ability and readiness of publishing municipal bonds in the West Sumatra Provincial Government as an alternative development financing. This analysis convers the province’s financial capacity West Sumatra through other ratio. This research uses descriptive quantitative approach. The result show that the government West Sumatra Province has the financial ability to issue regional bonds as indicated by the general revenue of the APBD in 2016 – 2020 not exceeding 75% of the total regional general revenue in the previous year and a DSCR analysis with yield >2,5 resulting in West Sumatra Province being prepared to issue bonds. Regions in the following year which is also supported by other ratio analysis, although the ratio of regional financial independence is still relatively low.